La metodología juego trabajo en el desarrollo de la convivencia en niños de 4 a 5 años de edad de la Unidad Educativa Ángel Polibio Chaves del cantón Guaranda, provincia Bolívar, periodo 2025 - Remache Aguay, Zulay Aracely (2025)
This research focuses on the play-work methodology in the development of social interaction among children aged 4 to 5 years at the "Ángel Polibio Cháves" educational unit, Bolívar Province, Guaranda Canton, period 2025, by addressing various fundamental topics for the development of emotional interaction. The research project used a mixed-method approach, as the data collection instruments were the observation form administered to the children and a survey administered to the teacher working at the institution. The research was conducted through observation within the "Ángel Polibio Cháves" educational unit. Therefore, it is necessary to understand the play-work methodology and how it is involved in the development of social interaction. To this end, the objectives were set, which were focused on solving the evident problem of poor social interaction among children aged 4 to 5 years. Considering that human beings are social beings who live in communities, by implementing the play-work methodology, children were given the opportunity to meaningfully learn about social and emotional relationships through play, thus achieving proper development of coexistence.